The role of acid sensing ion channels in the cardiovascular function - López-Ramírez, Omar; González-Garrido, Antonia (Frontiers in Physiology, 2023)
Acid Sensing Ion Channels (ASIC) are proton sensors involved in several physiological and pathophysiological functions including synaptic plasticity, sense of touch and nociception. ASIC channels have been ubiquitously localized in neurons and they play a modulatory role in their function. Thus, there is a great possibility that they also participate in cardiomyocyte function, as they are excitable cells as well. Experimental evidence places ASIC subunits in both plasma membrane and intracellular compartments of mammalian cardiomyocytes, suggesting they have several unrevealing functions in the cardiomyocyte physiology. ASIC channels are expressed in neurons of the peripheral nervous system including the nodose and dorsal root ganglia, both innervating the heart. In the cardiovascular system ASIC channels have a dual role as mechanosensors and chemosensors. In baroreceptor neurons from nodose ganglia, mechanosensation is directly associated with ASIC2a channels for proper detection of changes in arterial pressure. In dorsal root ganglia, ASIC2a/3 channel is the molecular sensor of cardiac ischemic pain for a number of reasons including its pH range activation, kinetics and the sustained current following its typical transient peak. This review consists of a summary of several reports about ASIC channels' role in the cardiovascular system and its innervation.